Energy loss of charged particles in anisotropic 2D materials using the oscillator model - Seguí, Silvina Tatiana; Gervasoni, Juana Luisa; Arista, Nestor Ricardo; Miskovic, Zoran L. (Pergamon-Elsevier Science Ltd, 2023)
Fil: Seguí, Silvina Tatiana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Física Enrique Gaviola. Universidad Nacional de Córdoba. Instituto de Física Enrique Gaviola; Argentina